The relationship between negative psychological state and quality of life among cardiovascular disease patients in China: the masking effect of abnormal dietary behavior - QingNing Chang; QingNing Chang; HaiBo Ma; Can Zhang; Xin Li; YiBo Wu; LiNa Ha (Frontiers in Cardiovascular Medicine)
BackgroundIt is well known that abnormal dietary behavior increases the risk for cardiovascular disease especially if the person is depressed and/or anxious. The purpose of this study was to construct a moderated mediation model to explore the roles of abnormal dietary behavior and family health in the mechanism through which depression/anxiety influences Quality of life (QoL) in patients with cardiovascular disease.MethodsA field survey was conducted in China and ultimately included 730 patients with cardiovascular disease aged 20–60 years. Data were collected using the Europe Quality of five-dimensional five-level questionnaire, Short-Form of the Eating Behavior Scale, Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, and the Chinese version of the short-form of the Family Health Scale. All data were analyzed using SPSS Statistics 23.0.Results(1) Depression was negatively associated with QoL (r = −0.386/−0.230, p < 0.001), and was positively correlated with abnormal dietary behavior (r = 0.377, p < 0.001). Anxiety was negatively associated with QoL (r = −0.383/−0.231, p < 0.001), and was positively correlated with abnormal dietary behavior (r = 0.333, p < 0.001). Abnormal dietary behavior was negatively correlated with QoL (r = −0.077/−0.119, p = 0.039/0.001). (2) In the mediation model, abnormal dietary behavior only had a masking effect on the relationship between depression and QoL, with a mediating effect size of 7.18%. The mediating effect of abnormal dietary behavior between anxiety and QoL was not significant. (3) The mediating effect size of abnormal dietary behavior between depression/anxiety and QoL increased to 14.77% and 13.57% in unhealthy families. The above masking mediation effect was not significant in healthy families.ConclusionsAbnormal dietary behavior positively mediated the relationship between depression and QoL and attenuated the negative effect of depression on QoL in patients with cardiovascular disease. The masking mediating effect of abnormal dietary behavior between depression/anxiety and QoL was stronger for patients in unhealthy families.